Peacebuilding: From the Women’s Perspective - Pun, Ekku Maya (Bodhi: An Interdisciplinary Journal, 2010)
Peace, the most sought after, the most discussed, the most expensive yet illusive and distant as ever is looking for the change in how it is perceived and how it can be achieved. Property, wealth and lives have been recklessly spent for it in vain. It is seeking an alternative method/s for its achievement. And I believe that alternative can be found in women's perspective of peace and their ways of attaining it. This article discusses the necessity to include feminine perspective in peacebuilding and argues why they are better suited to negotiate peace. DOI: 10.3126/bodhi.v2i1.2875 Bodhi Vol.2(1) 2008 p.224-259